Dinamika Pengasuhan Anak Usia Dini oleh Orang Tua Generasi Z dalam Menghadapi Tantangan di Era Digitalisasi - Zazkia Anzalna Lasifa; Wanodya Kusumastuti; Itsna Iftayani (Hadlonah: Jurnal Pendidikan dan Pengasuhan Anak, 2026)
This study aims to deeply understand the dynamics of early childhood parenting by Generation Z parents in the digital era. This study uses a qualitative phenomenological approach, data were collected through semi-structured interviews with parents born between 1997 and 2012. The results of this study indicate that Generation Z parents have good digital awareness, where technology is not only seen as a means of entertainment for children, but can also be used as a source of parenting literacy through critical selection. The main findings in this study reveal five adaptive strategies that can be applied, namely: setting limits on digital media use, accompanying and monitoring children when using digital media, active communication between parents to educate children about digital media, parents as role models in behavior using digital media, and providing emotional support and support in the good use of digital media. Although the technology-intensive social environment is a major challenge, Generation Z parents tend to adopt an open and responsive parenting style to balance children's developmental needs with the progress of the times and the values ​​​​that exist in the surrounding environment. This study emphasizes that the success of digital parenting in Generation Z depends on the ability of parents to integrate technological literacy with emotional attachment.